2022
DOI: 10.1109/tasc.2022.3151950
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Local Inhomogeneities in the REBCO Layer on the Mechanism of Quench Onset in 2G HTS Tapes

Abstract: The Resistive-type of Superconducting Fault Current Limiters (R-SFCL) using the second generation of hightemperature superconductors (2G HTS) are well adapted to power grid protection. Almost electrically invisible in normal operation, it quenches and becomes highly resistive in the event of a fault. The tape operation at the transition from the superconducting state to the resistive state is the basis of a R-SFCL. In this scope, we studied the onset of a quench occurring in 2G HTS tapes using high-speed imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…A similar evolution of a dissipation spot was also mentioned in [13]. Furthermore, in [7], it was shown that areas with low superconducting properties in a 2G HTS tape (determined with Scanning Hall Probe Microscopy) matched the positions of the dissipation columns.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…A similar evolution of a dissipation spot was also mentioned in [13]. Furthermore, in [7], it was shown that areas with low superconducting properties in a 2G HTS tape (determined with Scanning Hall Probe Microscopy) matched the positions of the dissipation columns.…”
Section: Resultssupporting
confidence: 77%
“…A high-speed Phantom V311 camera able to record one image every 20 µs was used to observe the bubble generation on the surface of the sample. More details are given about the experimental setup in [7].…”
Section: Methodsmentioning
confidence: 99%
“…With the breaking capacity of the breakers to be exceeded in the near future, fault-current limiting methods have become indispensable in recent years. One of the modern methods, SFCL, limits the fault current effectively and quickly by using the transition property between the superconducting and resistive regions of the superconducting material (Method, 2019) (Zampa et al, 2022). SFCL limits the fault current level and protects both breakers and other power system components (Ju et al, 2022) (Xiang et al, 2018) (Jiahui Zhu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Elimination of the mentioned disadvantages is possible by using SFCLs, which use the abrupt transition of superconducting material from superconducting to the resistive region at a specific critical current value (Nagarathna et al, 2015) (X. Chen et al, 2022) (Zampa et al, 2022). SFCLs are the best alternative to replace conventional limiting methods thanks to the advantages of superconducting materials (J.…”
Section: Introductionmentioning
confidence: 99%